Answer:
x=4
y=10
Step-by-step explanation:
3x +3y = 27
x - 3y = -11 (add these up so 3y will be eliminated and you'll have x only)
4x = 16
now let's eliminate x (you can put 4 instead of x though)
3x + 3y = 27
-3/ x -3y= -11 (multiple the the 2nd equation with -3 to eliminate x )
3x + 3y =27
-3x + 3y =33
6y = 60
Hi there! With equations like this we want to get our variable on one side and and our constant on the other.
So with 2x + 3 = -7 you'd subtract the constant 3 from both sides of the equal sign to get 2x = -10, then you'd divide both sides by 2 to get x = -5. If you double check your work by replacing x in the original equation with our answer we'd find that 2(-5) + 3 = -7 is correct.
Hope you find this helpful :)
Answer:
$2560+$1100=$3660
Step-by-step explanation:
$640×4=$2560 if the month is over and she is due a payment
5%×$22000=$1100 of sales if they are to be considerred and paid every month
Answer:
(e^3 / e^2n)
Step-by-step explanation:
isn't this the same question
Answer:
9.01 maybe my math might be wrong
Step-by-step explanation: